0–1 integer programming model for procedural separation of aircraft by ground holding in ATFM - Ozgur, Metin; Cavcar, Aydan (Aerospace science and technology, 2014)
This study presents a 0–1 integer programming model for air traffic flow management. The model is used for determining optimum departure times of aircraft so as to avoid aircraft conflicts and to balance capacity and demand on the airports. Standard air traffic control procedural separation minimas were set as conflict criteria, which has never been done before, and this makes it convenient for use in planning of flows in airspace sectors especially without surveillance system. The model was tested on an imaginary scenario, including an airspace sector, airport capacities and flight plans, and solved by a mathematical modelling and optimization software. Considering conflicts before takeoff, as in this study, might prevent riskier and costlier air traffic control measures such as heading, speed and flight level changes. The great need for these measures can be easily inferred from the solution results that presents delay times due to conflict related constraints. Utilizing both standard conflict criteria based on procedural separation minimas used in air traffic control and standard Air Traffic Flow Management strategy based on ground holding of aircraft in planning of flows, makes it easier to adapt the model to the current Air Traffic Flow Management system.